KOMPARASI ALGORITMA DENOISING DAN BINARIZATION DENGAN ADAPTIVE THRESHOLDING DAN MORFOLOGI UNTUK MENIGKATKAN KUALITAS KETERBACAAN CITRA NASKAH LONTAR (TAKEPAN) SASAK - SAMSU, L M; SAIFUL, MUHAMMAD; Bahtiar, Hariman (Fakultas Teknik Universitas Hamzanwadi, 2020)
One of the cultural heritages in West Nusa Tenggara, especially Lombok, is takepan (ancient lontar manuscripts). Takepan written on Lontar leaf sheets (Duntan leaf in Sasak language) is known as the jejawan script (derived from ancient Javanese language). According to [1] in his research on image segmentation of Javanese script, the adaptive thresholding value was obtained based on the variation in the sensitivity of each local windows. The process of determining the thresholding value works on blocks in the image. Images that have high contrast and high lighting variations are very difficult to classify as background or foreground because there are a lot of pixels, you should use Local Adaptive Thresholding. From the research that has been done, it can be concluded that adaptive thresholding and morphology with dilation approach really help maximize image readability with the highest Peak Signal to Noise Ratio (PSNR) value reaching 34,107 dBDOI : 10.29408/jit.v3i2.2304